Application of threshold vector error correction model (TVECM) in describing adjustment of interest rate of working capital credit to BI rate movement - Gama Putra Danu Sohibien (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2017)
Knowledge about bank behavior in adjusting the interest rate to BI rate movement is important not only for debtors to make a decision to borrow money, but also for government to know whether BI rate as a monetary policy tool success in influencing the movement of interest rate. The approach used for analyzing the data in this paper is TVECM. The data used in this paper are interest rate of working capital credit of conventional bank and BI rate of January 2008–July 2016. Bank is more agressive in correcting the disequilibrium by increasing the interest rate of working capital credit than decreasing it. Interest rate of working capital credit is significantly adjusted by bank approximately 64.95% of its disequilibrium when the disequilibrium is lower than 0.96. When it is between 0.96 and 0.76, interest rate of working capital credit will be adjusted approximately 11.87% of its disequilibrium.When it is higher than 0.76, interest rate of working capital credit will be adjusted approximately 11.88% of its disequilibrium. Moderate interest rate of working capital credit based on BI rate consideration is between 1.74 BI rate –0.96 and 1.74 BI rate +0.76. According to the selection criteria values, TVECM is better than VECM and VAR in modeling relationship between BI rate and interest rate of working capital.